The Fate of Oil in the Water Column Following Experimental Oil Spills in the Arctic Marine Nearshore - Humphrey, B.; Green, D.R.; Fowler, B.R.; Hope, D.; Boehm, P.D. (ARCTIC, 1987)
Petroleum hydrocarbon concentrations in the water column were monitored after a release of crude oil onto the water surface and a subsurface release of chemically dispersed oil. During the surface release, petroleum hydrocarbons did not disperse into the water column deeper than 1 m. The highest concentrations observed under the slick were less than 2 mg/l. The chemically dispersed oil released resulted in concentrations over 50 mg/l in the Bay 9 study area for 12 hours. Estimated exposures of the benthic communities to oil in the three experimental bays were 3 mg/l/h, 30 mg/l/h, and 300 mg/l/h respectively. The highest exposures were to oil retaining many of its more toxic components.Key words: dispersant, oil, fluorometry, gas chromatography, oil spill Mots clés: agent de dispersion, fluorométrie, chromatographie en phase gazeuse, déversement de pétrole